Retinoblastoma, the African Context - Essuman, V.A.; Beyuo, V.M.; Dimaras, H. (Book cover Global Perspectives in Ocular Oncology, 2023)
Retinoblastoma is the commonest intraocular childhood cancer in the world with an incidence of 1 in 15,000–20,000. Of the global retinoblastoma population, 28% is found in sub-Saharan Africa. Prognosis is good but is uniformly fatal if not detected early and appropriate treatment applied. While survival rates in some developed countries such as the United States and Canada are nearly 100%, survival rates from Africa are still very low mostly due to late disease presentation. Lack of awareness of the disease and its outcome, failure to recognize early warning signs, parental preference to seek alternative medicine in the form of spiritual and/or herbal treatment first, difficulty in accessing referral centres and financial constraints are some contributory factors to late disease presentation. Enucleation with or without systemic chemotherapy remains the mainstay of management in most African countries. Though Africa has seen some improvement in retinoblastoma outcomes, early detection, partnerships for capacity building, funding and research are some areas that need to be improved upon to achieve higher survival rates. This chapter focuses on the challenges of retinoblastoma management and tangible opportunities for progress in the African context.
Research Article
Keywords: Retinoblastoma; Leukocoria; Orbital retinoblastom